Identification of Modal Frequencies From the Pre-Stressed Concrete Bridge Dynamic Response to Different Sources of Dynamic Excitation - Melcer, Jozef; Kortis, Jan; Daniel, Lubos; Fabo, Peter (Communications - Scientific Letters of the University of Zilina, 2018)
The natural frequencies and mode shapes are unique characteristics of each mechanical structure. Their prediction is a crucial part of each dynamic experimental measurement. However, the proper identification of higher natural frequencies and mode shapes can be a problem, especially for big structures such as bridges. The reason is the need to excite the bridge in such a way that it responds in a free-vibrations mode shape. This paper describes three various sources of excitations, which are used to identify the modal characteristics of the pre-stressed concrete bridge. The impulse excitation, traffic load and ambient vibration are used and analyzed. In the case of the loading by a force impulse, modal shapes are also obtained. The study shows that the intensity and kind of the excitation has a noticeable impact on identification of modal frequencies. Finally, the results of the experimental measurements are used to calibrate the numerical model.
Keywords: dynamic excitation; modal frequencies; free vibrations; moving load; FRF function